2013
DOI: 10.1080/10810730.2013.778365
|View full text |Cite
|
Sign up to set email alerts
|

The Montana State University Conceptual Model of Complementary and Alternative Medicine Health Literacy

Abstract: This article aims to present and describe a model of complementary and alternative medicine (CAM) health literacy. The model is the conceptual basis for CAM health literacy, which is operationally defined as the information about CAM needed to make informed self-management decisions regarding health. Improving health literacy is a national priority, and widespread use of CAM has added to the complexity of this task. There are no currently available models or measures of health literacy regarding CAM. The autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…Of the 22 models included in the literature review, most were based on existing literature on health literacy [ 7 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Others were primarily based on more general theories and concepts [ 8 , 22 , 23 , 24 , 25 ], concept mapping [ 26 ], practical experiences [ 27 ], or combinations of these sources [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 22 models included in the literature review, most were based on existing literature on health literacy [ 7 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Others were primarily based on more general theories and concepts [ 8 , 22 , 23 , 24 , 25 ], concept mapping [ 26 ], practical experiences [ 27 ], or combinations of these sources [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the characteristics of the models, 16 primarily focused on associations of health literacy with determinants and outcomes [ 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 27 , 29 ], and of these, 15 included determinants of health literacy at the level of the individual (e.g., educational level, age, cognitive skills) [ 7 , 8 , 9 , 11 , 12 , 13 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 27 , 29 ]. Most of these models also included intermediate outcomes between health literacy and health outcomes (e.g., knowledge, health behaviors, self-care) [ 7 , 8 , 9 , 11 , 12 , 13 , 16 , 18 , 19 , 20 , 21 , 27 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of adults older than 65 years are seeking information on the internet [ 26 ], with 38% of seniors using the internet; however the majority (75%) do not consistently check the source and date of information found. Responses from interviews also indicated that the information on the internet frequently influenced CM decision-making, and Shreffler-Grant et al have identified that many of these sites make unsubstantiated claims to treat, prevent, diagnose, and/or cure specific diseases [ 27 ]. Low health literacy around these domains highlights the potential for older vulnerable people to be misinformed and to make inappropriate self-care decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The research team developed a conceptual model of CAM health literacy to guide the development of a measure of CAM health literacy (Shreffler-Grant, Nichols, Weinert, & Ide, 2013b). The model was constructed through a lengthy iterative process of deriving constructs, concepts, and empirical indicators from the literature and the research team’s prior work, review and critique by experts, and extensive revision.…”
Section: Conceptual Considerationsmentioning
confidence: 99%